Brucella abortus Infection Modulates 3T3-L1 Adipocyte Inflammatory Response and Inhibits Adipogenesis - Pesce Viglietti, Ayelén Ivana; Giambartolomei, Guillermo Hernán; Quarleri, Jorge; Delpino, María Victoria (Frontiers in Endocrinology, 2020)
Brucellosis is a prevalent global zoonotic infection but has far more impact in developing countries. The adipocytes are the most abundant cell type of adipose tissue and their secreted factors play an important role in several aspects of the innate and adaptive immune response. Here we demonstrated the ability of Brucella abortus to infect and replicate in both adipocytes and its precursor cells (pre-adipocytes). Additionally, infection of pre-adipocytes also inhibited adipogenesis in a mechanism independent of bacterial viability and dependent on lipidated outer membrane protein (L-Omp19). B. abortus infection was able to modulate the secretion of IL-6 and the matrix metalloproteases (MMPs) -2 and-9 in pre-adipocytes and adipocytes and also modulated de transcription of adiponectin, leptin and resistin in differentiated adipocytes. B. abortus-infected macrophages also modulate adipocyte differentiation involving a TNF-α dependent mechanism, thus suggesting a plausible interplay between B. abortus, adipocytes, and macrophages. In conclusion, B. abortus is able to alter the adipogenesis process in adipocytes and its precursors directly after their infection, or merely their exposure to the B. abortus lipoproteins, and indirectly through soluble factors released by B. abortus-infected macrophages.